Identity-based efficient authentication and key agreement protocol for mobile Internet - Zhen WANG; Zhao-feng MA; Shou-shan LUO (Tongxin xuebao)
For the bad computation overhead of bi1inear pairings in e11iptic curve and the prob1ems of certificate management in the PKI，an efficient and secure authentication key agreement protoco1 was proposed based on the identity-based cryptosystem and GDH difficu1t prob1em on the additive group of e11iptic curve.Meanwhi1e，the security of the new protoco1 was proved under the random orac1e mode1.The ana1ysis shows that the new protoco1 meets security properties such as known session key security，perfect forward security，ephemera1 secret 1eakage resistance and the session key escrow resistance.The proposed protoco1 has the good computationa1 overhead for it was ab1e to comp1ete the mutua1 authentication and session key agreement between parties under on1y 5 times sca1ar mu1tip1ication.